Avaliação do desempenho de pavimentos flexíveis do bairro de Batista Campos em Belém/PA mediante ao cálculo do índice de condição do pavimento - NEVES, Lucas Natanael Ferreira (2023)
The Urban Pavement Management System (SGPU) is a set of strategies that monitor and try to predict the performance of the pavement, directing the priorities of maintenance and rehabilitation activities, ensuring the effective use of public resources. However, the SGPU requires systematic data collection on the road network. Inserted in this context, this work is the fourth of a line of research whose objective is to evaluate the performance of the road network of the neighborhood of Batista Campos in Belém-PA between the years 2021 to 2023 through the calculation of the Pavement Condition Index (PCI). To this end, objective evaluations of the rolling surface condition were performed and the ICPs were calculated according to Sousa's (2021) method that adapted the Strategic Highway Research Program (SHRP) method. The 2023 ICPs were then compared with the 2021 and 2022 ICPs previously collected in this line of research. The main results were: The average PCI of the Batista Campos neighborhood decreased from 79.89 (2021) to 71.96 (2023), a reduction of 9.93%. The arterial roads of the neighborhood have the highest average ICP in the three years (76.06 - 2023, 81.40 - 2022 and 88.45 - 2021) when compared to the collector roads (69.34 - 2023, 70.67 - 2022 and 78.78 - 2021) and local (72.00 - 2023, 71.40 - 2022 and 77.45 - 2021). The most frequent defects of the road network analyzed in 2023 were patches (87.32%), wear (83.80%) and cracks due to fatigue (69.01%), which corroborates the surveys of previous years. São Silvestre Street presented the highest positive mean variation (21.52%) and Avenida 16 de Novembro presented the highest negative mean variation (-26.94%) in 2023, different from the previous year, whose street with the highest positive average variation was Avenida 16 de Novembro (5.71%) and the highest negative mean variation was Guilherme Seixas Street (-20.11%). Finally, it was concluded that the performance of the pavements of the neighborhood of Batista Campos, in general, decreased over the years and from the present work it was possible to verify the stretches that should be prioritized for future maintenance and rehabilitation activities.